2022
DOI: 10.3390/nu14122521
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Dietary Fiber Intake in Three Meals with All-Cause and Disease-Specific Mortality among Adults: The U.S. National Health and Nutrition Examination Survey, 2003–2014

Abstract: The timing of food intake can significantly alter the body’s metabolism of nutrient intake and affect the occurrence of chronic diseases. However, whether and how the intake time of dietary fiber could influence mortality risks is largely unknown. This study aims to reveal the association between total dietary fiber intake and fiber intake at different times with all-cause, cancer, and cardiovascular disease (CVD) mortality rates. A total of 31,164 adults who enrolled in the National Health and Nutrition Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Too low carbohydrate intake might correlate with trends of diseases such as insulin resistance and metabolic acidosis in healthy lean individuals [ 25 ]. Dietary fiber is a class of carbohydrate polymers, which is associated with the risk and prognosis of multiple chronic diseases [ 26 , 27 ]. In a previous study, the researchers found that higher total dietary fiber intake had a moderate effect on reducing hip bone loss in males, while vegetable fiber exhibited significant protective effects against spinal bone loss in females [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Too low carbohydrate intake might correlate with trends of diseases such as insulin resistance and metabolic acidosis in healthy lean individuals [ 25 ]. Dietary fiber is a class of carbohydrate polymers, which is associated with the risk and prognosis of multiple chronic diseases [ 26 , 27 ]. In a previous study, the researchers found that higher total dietary fiber intake had a moderate effect on reducing hip bone loss in males, while vegetable fiber exhibited significant protective effects against spinal bone loss in females [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple epidemiological investigations have reported that high intake of dietary fiber can reduce the risk of obesity, cardiovascular disease, chronic obstructive pulmonary disease, and diabetes [32]. Furthermore, high dietary fiber intake was associated with reduced all-cause cardiovascular disease and cancer mortality risk according to several cohort studies [33]. Numerous animal studies have demonstrated that SCFAs produced by fermentation of intestinal dietary fiber are associated with reductions in inflammatory responses, oxidative stress, immune responses, and apoptosis [10,21].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that obesity is accompanied by dysbiosis of gut microbiota, although no consensus has been formed on. It has been reported that a decrease in Bacteroidetes and an increase in Firmicutes are related to obesity 67 . A cohort study following weight‐loss bariatric surgery found patients with less favorable outcomes had oral microbiota enriched in phylum Actinobacteria and intestinal microbiota enriched in phylum Bacteroidetes 68 .…”
Section: Diseases Mediated By Gut Microbiota–tlrs Interplaymentioning
confidence: 99%
“…It has been reported that a decrease in Bacteroidetes and an increase in Firmicutes are related to obesity. 67 A cohort study following weight‐loss bariatric surgery found patients with less favorable outcomes had oral microbiota enriched in phylum Actinobacteria and intestinal microbiota enriched in phylum Bacteroidetes . 68 Nirmalkar et al further showed that the genus Lactobacillus and family Coriobacteriaceae were enriched in children, and genera Collinsella and Prevotella were enriched in obese adolescents.…”
Section: Diseases Mediated By Gut Microbiota–tlrs Interplaymentioning
confidence: 99%